2021
DOI: 10.3390/ijerph18168264
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Extended Spectrum Beta Lactamase (ESBL) Producers, Quinolone and Carbapenem Resistant Enterobacteriaceae Isolated from Environmental Samples along Msimbazi River Basin Ecosystem in Tanzania

Abstract: We conducted environmental surveillance of antimicrobial resistance (AMR) bacteria in the Msimbazi river basin in Tanzania to determine the occurrence of extended-spectrum β-lactamase (ESBL)-producing, carbapenem resistant Enterobacteriaceae (CRE) and quinolone resistant Escherichia coli and Klebsiella spp. A total of 213 Enterobacteriaceae isolates were recovered from 219 samples. Out of the recovered isolates, 45.5% (n = 97) were Klebsiella pneumoniae and 29.6% (n = 63) were Escherichia coli. K. pneumoniae i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
(66 reference statements)
1
10
0
Order By: Relevance
“…These ESBL organisms could easily spread from the vendors to the meat and, finally, to consumers in the food chain. ESBL organisms found in environmental samples along the Msimbazi River Basin Ecosystem in Tanzania were resistant to more than three classes of the antibiotics tested [ 5 ]. In another study in an urban study site in Keko Machungwa, part of the most significant unplanned and under-serviced settlement in Temeke district, Dar es Salaam, Tanzania, ESBL-producing Enterobacteriaceae were confirmed in 24.3% of the 70 latrine samples [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These ESBL organisms could easily spread from the vendors to the meat and, finally, to consumers in the food chain. ESBL organisms found in environmental samples along the Msimbazi River Basin Ecosystem in Tanzania were resistant to more than three classes of the antibiotics tested [ 5 ]. In another study in an urban study site in Keko Machungwa, part of the most significant unplanned and under-serviced settlement in Temeke district, Dar es Salaam, Tanzania, ESBL-producing Enterobacteriaceae were confirmed in 24.3% of the 70 latrine samples [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that E. coli's high agility in exchanging genetic information with various species is not uncommon. The increased presence of E. coli in nature can partly explain this finding [ 5 ]. The percentage of isolates expressing ESBL production is variable, as revealed by several previous studies: in the United States is 9.2%, Argentina (48%), France (11.4%), and India (68%), which is relatively similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We cannot rule out that some medicines, such as tetracyclines may have been used in veterinary farming. Indeed, some samples obtained from animals and the environment in the Msimbazi River basin in Tanzania indicated high resistance levels to some antibiotics classes used by humans [40,[42][43][44][45], such as tetracycline, nalidixic acid, ampicillin, and trimethoprim and sulfamethoxazole. These studies also revealed that farmers purchase these medicines without veterinary prescriptions [40,[42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…The Msimbazi river basin in Tanzania has a myriad of human activities making it a hot spot for the spread AMR bacteria and resistant genes between human-animal-environmental compartments [39][40][41][42]. Phenotypic studies conducted in the basin showed very high levels of ESBL producing and quinolone resistant strains among bacteria isolated from poultry, domestic pigs and the environment [43,44]. However, all these studies were limited to phenotypic screening of antibiotic resistant pathogens and none focused on the occurrence of resistant genes.…”
Section: Introductionmentioning
confidence: 99%